Effect of a Manager Training and Certification Program on Food Safety and Hygiene in Food Service Operations - Hailu Kassa; Gary S. Silverman; Karim Baroudi (SAGE Publishing, 2010)
Food safety is an important public health issue in the U.S. Eating at restaurants and other food service facilities increasingly has been associated with food borne disease outbreaks. Food safety training and certification of food mangers has been used as a method for reducing food safety violations at food service facilities. However, the literature is inconclusive about the effectiveness of such training programs for improving food safety and protecting consumer health. The purpose of this study was to examine the effect of food manger training on reducing food safety violations. We examined food inspection reports from the Toledo/Lucas County Health Department (Ohio) from March 2005 through February 2006 and compared food hygiene violations between food service facilities with certified and without certified food managers. We also examined the impact on food safety of a food service facility being part of a larger group of facilities. Restaurants with trained and certified food managers had significantly fewer critical food safety violations but more non-critical violations than restaurants without certified personnel. Institutional food service facilities had significantly fewer violations than restaurants, and the number of violations did not differ as a function of certification. Similarly, restaurants with many outlets had significantly fewer violations than restaurants with fewer outlets, and training was not associated with lower numbers of violations from restaurants with many outlets. The value of having certified personnel was only observed in independent restaurants and those with few branches. This information may be useful in indicating where food safety problems are most likely to occur. Furthermore, we recommend that those characteristics of institutional and chain restaurants that result in fewer violations should be identified in future research, and efforts made to apply this knowledge at the level of individual restaurants.